SELECTION OF VIDEO CONFERENCE APPLICATION FOR MATHEMATICS LEARNING USING INTUITIONISTIC FUZZY MAX-MIN AVERAGE COMPOSITION METHOD - Henra, Kiki; Efuansyah, Efuansyah; Sulaiman, Raden (PATTIMURA UNIVERSITY, 2023)
In this article, the Intuitionistic Fuzzy Max-Min Average Composition method is used which aims to choose the right video conferencing application for learning mathematics. The results show that the learning process in Mathematical economics, Calculus, Statistics, and Geometry courses is more appropriate using the Microsoft Teams video conferencing application than Zoom and Google Meet.